Rules and the Containment of Conflict in Congress. Issue 4 (9th January 2022) - Fong, Christian
Abstract : Congressional rules can be violated by majority vote, but the application of those rules often leads to different outcomes than would prevail under direct majority rule. Why does Congress enact rules in the first place, and why would not a majority violate those rules whenever it disliked the outcomes they produced? Drawing from work in psychology, I argue legislators become angry and engage in socially costly retaliation when unfavorable outcomes are produced by discretionary authority but not when they are produced by the application of fixed rules. Consequently, rules sometimes inefficiently allocate congressional resources, but they also reduce costly conflict within the institution. I present a model that provides conditions under which the legislature prefers to enact and defer to rules and derive its empirical implications.